2019
DOI: 10.1017/s0031182019001586
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of viable Toxoplasma gondii from the first national survey of feral swine revealed evidence for sylvatic transmission cycle, and presence of highly virulent parasite genotypes

Abstract: Feral swine are known reservoirs of various pathogens, including Toxoplasma gondii. Here, we report the first national survey of viable T. gondii in feral swine in the USA. We paired serological surveys with parasite isolation and bioassay to evaluate the prevalence and genetic diversity of these parasites. From 2012–2017, sera and tissues from 1517 feral swine across the USA were collected for the isolation of viable T. gondii. Serum samples were initially screened for antibodies to T. gondii, and then the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
2
20
0
1
Order By: Relevance
“…MAT using a 1:25 cut‐off has been used extensively for the diagnosis of T. gondii infection in both domestic and wildlife species (reviewed by Almeria et al., 2018; Dubey, 2010). Although there are no recent experimental infections, two large studies in feral swine and in deer in the USA showed evidence for the validity of serological analysis by MAT since viable T. gondii was isolated from a large number of seropositive animals and the rate of isolating viable parasites was positively associated with MAT titres in those studies (Dubey et al., 2020a, 2020b, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…MAT using a 1:25 cut‐off has been used extensively for the diagnosis of T. gondii infection in both domestic and wildlife species (reviewed by Almeria et al., 2018; Dubey, 2010). Although there are no recent experimental infections, two large studies in feral swine and in deer in the USA showed evidence for the validity of serological analysis by MAT since viable T. gondii was isolated from a large number of seropositive animals and the rate of isolating viable parasites was positively associated with MAT titres in those studies (Dubey et al., 2020a, 2020b, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…This technique has been employed broadly for the diagnosis of antibodies against T. gondii in both domestic and wildlife species [1]. Two recent large studies in wild pigs and white-tailed deer in the USA added evidence for the validity of serological analysis by MAT in those species since viable T. gondii was isolated from a large number of seropositive animals and the rate of isolating viable parasites was positively associated with MAT titers in those studies [30][31][32][33]. Each serum sample was tested at 1:25 and 1:50 dilutions, including positive and negative controls in each test.…”
Section: Serological Testingmentioning
confidence: 99%
“…Population genetics may also be used to understand disease in the context of short time frames such as the description of pathogen life cycles (including the study of alternative hosts or reservoirs). While such studies on pathogen reservoirs have been frequently conducted with regard to human or livestock pathogens (e.g., Dubey et al, 2020; Venkatesan & Rasgon, 2010) they have scarcely been conducted for wildlife pathogens. However, the knowledge on pathogen lifecycles and reservoirs is indispensable if we are to understand wildlife diseases, develop possible management strategies or indeed avoid the further spread of pathogens (e.g., from caving equipment in the case of P. destructans; Zhelyazkova et al, 2020; Zhelyazkova et al, 2019).…”
Section: Discussionmentioning
confidence: 99%